The role of the Mediterranean diet in reducing the risk of cognitive impairement, dementia, and Alzheimer’s disease: a meta-analysis - Fekete, Mónika; Varga, Péter; Ungvari, Zoltan; Fekete, János Tibor; Buda, Annamaria; Szappanos, Ágnes; Lehoczki, Andrea; Mózes, Noémi; Grosso, Giuseppe; Godos, Justyna; Menyhart, Otilia; Munkácsy, Gyöngyi; et al. (GeroScience, 2025)
Age-related cognitive impairment and dementia pose a significant global health, social, and economic challenge. While Alzheimer’s disease (AD) has historically been viewed as the leading cause of dementia, recent evidence reveals the considerable impact of vascular cognitive impairment and dementia (VCID), which now accounts for nearly half of all dementia cases. The Mediterranean diet—characterized by high consumption of fruits, vegetables, whole grains, fish, and olive oil—has been widely recognized for its cardiovascular benefits and may also reduce the risk of cognitive decline and dementia. To investigate the protective effects of the Mediterranean diet on cognitive health, we conducted a systematic literature review using PubMed, Web of Science, and Google Scholar, focusing on studies published between 2000 and 2024. The studies included in the meta-nalysis examined the adherence to the Mediterranean diet and the incidence of dementia and AD. We applied a random-effects model to calculate pooled hazard ratios (HRs) with 95% confidence intervals (CIs) and assessed heterogeneity through I -square statistics. Forest plots, funnel plots, and Z -score plots were used to visualize study outcomes. Of the 324 full-text records reviewed, 23 studies met the inclusion criteria. The combined HR for cognitive impairment among those adhering to the Mediterranean diet was 0.82 (95% CI 0.75–0.89); for dementia, the HR was 0.89 (95% CI 0.83–0.95); and for AD, the HR was 0.70 (95% CI 0.60–0.82), indicating substantial protective effects. Significant heterogeneity was observed across studies, though Z -score plots suggested sufficient sample sizes to support reliable conclusions for each condition. In conclusion, this meta-analysis confirms that adherence to the Mediterranean diet is associated with an 11–30% reduction in the risk of age-related cognitive disorders, including cognitive impairment, dementia, and AD. These findings underscore the Mediterranean diet’s potential as a central element in neuroprotective public health strategies to mitigate the global impact of cognitive decline and dementia and to promote healthier cognitive aging.